Risk factors for recurrence after surgical repair of coarctation of the aorta in children: a single-center experience based on 51 children - Zhao, Zhenjiang; Pan, Zhengxia; Wu, Chun; Tian, Jie; Qin, Jinjie; Zhang, Yulin; Jin, Xin (Frontiers in Cardiovascular Medicine, 2023)
Background: Coarctation of the aorta (CoA), is a congenital malformation, often combined with several cardiac abnormalities. At present, the operation effect is satisfactory, but postoperative restenosis is still a matter. Identification of risk factors for restenosis and prompt therapy adjustments may improve patient outcomes. Materials and methods: A retrospective clinical study of patients under 12 who had CoA repair in 2012-2021, with a randomized cohort population of 475 patients. Results: A total of 51 patients (M/F: 30/21) with a mean age of 5.33 (2.00-15.00) months and a median weight of 5.60 (4.20-10.00) kg. The mean follow-up was 8.93 (3.77-19.37) months. Patients were divided into 2 groups: no-restenosis (n-reCoA) (G1, 38 patients) and restenosis (reCoA) (G2, 13 patients). ReCoA was defined as a restenosis requiring interventional or surgery or a pressure gradient >20 mmHg at the repair site as reported by B-ultrasound with the presence of an upper and lower limb blood pressure gradient or growing dysplasia. The overall reCoA incidence was 25% (13/51). In multivariate COX regression, smaller preoperative z-score of the ascending aorta (P=0.009, HR=0.68) and transverse aortic arch (P=0.015, HR=0.66), arm-leg systolic pressure gradient ≥12.5 mmHg at discharge (P=0.003, HR=1.09) were independent risk factors for reCoA. Conclusion: The overall outcome of CoA surgery is successful. Smaller preoperative z-score of the ascending aorta and transverse aortic arch, and an arm-leg systolic pressure gradient ≥12.5 mmHg at discharge increase reCoA risk, and closer follow-up for such patients are required especially within 1 postoperative year.